2015
DOI: 10.1242/jcs.165803
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional activator Gli2 modulates T-cell receptor signalling through attenuation of AP-1 and NFκB activity

Abstract: Different tissues contain diverse and dynamic cellular niches, providing distinct signals to tissue-resident or migratory infiltrating immune cells. Hedgehog (Hh) proteins are secreted inter-cellular signalling molecules, which are essential during development and are important in cancer, post-natal tissue homeostasis and repair. Hh signalling mediated by the Hh-responsive transcription factor Gli2 also has multiple roles in T-lymphocyte development and differentiation. Here, we investigate the function of Gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 74 publications
2
53
0
Order By: Relevance
“…A third possibility is that the IFITM proteins are involved in enhancing or regulating the transduction of other signalling pathways that regulate Th differentiation. In support of this, they are transcriptional targets of Wnt and Hh signalling, 10,11 and both these pathways promote Th2 differentiation. 72,74,85,86 Finally, it is possible that the IFITM proteins have unknown direct consequences for Th differentiation through an influence on transcription or translation (as has been described for some viral genes).…”
Section: Mechanisms Of Action Of Ifitm Proteins In Immune Cellsmentioning
confidence: 84%
See 3 more Smart Citations
“…A third possibility is that the IFITM proteins are involved in enhancing or regulating the transduction of other signalling pathways that regulate Th differentiation. In support of this, they are transcriptional targets of Wnt and Hh signalling, 10,11 and both these pathways promote Th2 differentiation. 72,74,85,86 Finally, it is possible that the IFITM proteins have unknown direct consequences for Th differentiation through an influence on transcription or translation (as has been described for some viral genes).…”
Section: Mechanisms Of Action Of Ifitm Proteins In Immune Cellsmentioning
confidence: 84%
“…Gene and protein expression studies have demonstrated that IFITM1-3 are expressed in murine CD4 + and CD8 + T cells. 7,11,13,37 Expression of Ifitm2 and Ifitm3 are regulated by TCR signalling. 13 In naive CD4 + T cells, RNA sequencing showed that expression of Ifitm3 was rapidly down-regulated during the first 24 hr after activation by anti-CD3/CD28 ligation in T helper type 0 (Th0), Th1 and Th2 culture conditions, whereas Ifitm2 was up-regulated and its expression continued to rise for the first 3 days after activation and levels of Ifitm1 were low and were not changed by TCR signalling.…”
Section: Ifitm Expression In Murine T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome‐wide association studies (GWAS) have indicated that the Hedgehog (Hh) signaling pathway plays a role in allergic asthma and experimental mouse asthma studies have shown that increased Hh signaling to T cells and eosinophils exacerbates the disease . Consistent with the reduction in allergic airways disease observed in the IfitmF ‐deficient mice, both Ifitm2 and Ifitm3 are Hh‐target genes in CD4 + T cells . In the future, it will be interesting to dissect the interactions between Hh pathway activation and IFITM function in asthma.…”
Section: Discussionmentioning
confidence: 99%